SOCIAL ENTREPRENEURSHIP IN THE WORLD: PROBLEMS AND PROSPECTS - MURADOV, R.R (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2021)
The imperfection of the market economy and administrative methods of economic management gives rise to the idea of reorientation to the social market model of economic development. In the USA, the state, both morally and financially, actively supports social entrepreneurship at all levels of government, which helps to save significant budgetary funds. In the EU states, it is viewed as the most important sphere of state social policy. In Asian countries, joint ventures are developed by individuals in the form of charitable activities, morally and sometimes legally supported by the state. Azerbaijan should learn from the experience of advanced foreign countries in the development of social entrepreneurship, although we still have to overcome cultural, economic and institutional barriers on this path.